Back Cover. Issue 5 (24th January 2022) - Unknown
Abstract : We developed an efficient radical approach for the selective cleavage of a single C—F bond of 3, 3‐difluorooxindoles, providing a powerful route to access valuable 3‐substituted 3‐fluorooxindoles. Mechanistically, a boryl radical attacks the carbonyl oxygen atom of the amide group and then induces a spin center shift process to break the C—F bond. More details are discussed in the article by Wang et al. on page 577—581. Abstract : We developed an efficient radical approach for the selective cleavage of a single C—F bond of 3, 3‐difluorooxindoles, providing a powerful route to access valuable 3‐substituted 3‐fluorooxindoles. Mechanistically, a boryl radical attacks the carbonyl oxygen atom of the amide group and then induces a spin center shift process to break the C—F bond. More details are discussed in the article by Wang et al. on page 577—581.